Response of Oil Production and Quality to Hedgerow Design in Super-High-Density Olive cv. Arbequina Orchards - Trentacoste, Eduardo Rafael; Connor, David J.; Gómez del Campo, María (MDPI, 2021)
An analysis is presented of the response of olive oil production and quality parameters, viz. fatty acids (palmitic, oleic and linoleic acids), phenolic compounds and oxidative stability to hedgerow spacing and orientation in 1-m wide super-high-density orchards of cv. Arbequina. Data reveal strong linear relationships between concentrations of fatty acids and internal irradiance within hedgerows, positive for palmitic and linoleic but negative for oleic acid. The result is a significant vertical trend in oil composition within hedgerows, but small to negligible differences in oil harvested from them in totality. The explanation is found in the small ranges and strongly correlated responses of individual fatty acids that together comprise 98% of oil mass. Phenolic compounds respond more widely and to higher levels of irradiance than fatty acids and did show increases in NS hedgerows grown at wide row spacing. Oxidative stability shows a similar trend in phenolic compounds. A simulation study that extended the known responses to 2-m wide hedgerows showed that the linkage between fatty acid profiles was maintained with no resultant differences in the oil composition of the total simulated oil harvest. Based on the current understanding of internal irradiance within olive hedgerows, there seems to be little opportunity to manage oil quality by orchard structure.